Family functionality and influence on the alcohol consumption of university students - Bárcenas Santana, Susana (2022)
Objective: To determine the family functionality and the influence of alcohol consumption within the family on the alcohol consumption of university students. Method: A descriptive quantitative cross-sectional study in a sample of n= 50 students from the health area. The confidentiality of the participants' data was ensured and the Family APGAR instrument was used to determine the student's perception of family functionality and the Alcohol use Disorder Identification Test Questionnaire to measure alcohol consumption. Frequency distributions were made for the qualitative variables and measures of central tendency and variability for the quantitative ones. Main results: The female gender prevailed 72%, the average age was 19.46 years of age (SD = ± 1.72), 48% of the students belonged to non-alcohol consuming families and 72% of the participants concerned highly functional families, 62% of the students were placed in the consumption of alcohol without risk and regarding the influence that alcohol consumption within the family has on student consumption, a greater tendency to have a safe alcohol consumption was observed when no family member is a consumer 36% (X2 = 14.19; p = 0.027). Overall conclusion: Parents play a very important role in promoting healthy or unhealthy behaviors, as young people try to imitate their behaviors.